Endocrine response to physical restraint and isolation in blue-fronted parrots - Queiroz, Carla M. [UNESP]; Santos, Gisele J. [UNESP]; Destro, Flavia C. [UNESP]; Teixeira, Carlos R. [UNESP]; Pantoja, José C. [UNESP]; Schmidt, Elizabeth M.S. [UNESP]; Palme, Rupert; Ferreira, João C.P. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate the response of blue-fronted parrots to restraint procedures and separation by non-invasive methods such as measurement of glucocorticoid metabolites in droppings. For this, we utilized 24 birds, 17 males and 7 females, initially kept in large adjacent aviaries, separated by sex. After capture and 3 minutes of manual contention, by random, 13 birds returned to the aviary and 11 animals were housed in individual cages in the same facility of the aviaries allowing the maintenance of auditory and visual contact between them. In order to evaluate if the physically isolated birds isolated or in groups would react in different ways, all droppings samples were collected at 3-hours intervals during 24 hours to evaluation of excreted glucocorticoid metabolites by enzimeimmunoassay. There were no significant effects of sex (P=0.5850), treatment (P=0.6805) and time (P=0.2293) and the glucocorticoid metabolites concentrations were within the diurnal range expected for this specie. Therefore, the endocrine response of both groups was similar and stress of capture and physical separation was not significant for the birds.
Resposta endócrina à contenção física e isolamento em papagaios-verdadeiros
Keywords: Amazona aestiva; Glucocorticoid metabolites; Stress; Welfare